Proliferation and differentiation potential of rat forebrain oligodendroglial progenitors both in vitro and in vivo. - Hardy,R; Reynolds,R (Development, 1991)
We have followed the development of the O-2A progenitor cell from the neonatal rat forebrain, both in dissociated cell culture and in cryostat sections, using immunocytochemical techniques employing a panel of antibodies that recognise the cells at different stages of their development. This included the monoclonal antibody LB1, which binds to the surface ganglioside GD3 expressed on O-2A progenitor cells. In secondary cultures enriched for O-2A progenitors maintained in a serum-free chemically defined medium, a large proportion of the cells are primed to differentiate into oligodendroglia and go on to express the oligodendroglial specific surface glycolipid galactocerebroside (GC) and then the myelin proteins CNP and MBP. However, a significant proportion of immature bipolar GD3+ cells remained after 6 days in secondary culture. It appears that not all the O-2A progenitors in our cultures differentiate immediately and some cells remain in an undifferentiated state and divide to replenish progenitor numbers. We have also identified in our cultures a small apolar GD3- cell, which when isolated differentiated into a GD3+ bipolar O-2A progenitor cell. We have termed this cell type a preprogenitor. The differentiation of this cell type into O-2A progenitors may be the source of the immature GD3+ cells present at the later stages of our secondary cultures. The proliferative profile of the cultures was studied using 5'bromo-2-deoxyuridine (BrdU) incorporation as an index of mitosis. Only the immature, bipolar O-2A progenitors were seen to divide at any time in serum-free culture. Neither the more mature multipolar O-2A cells nor the oligodendroglia were seen to divide. The developmental profile of the O-2A cells in the rat forebrain in vivo showed a largely similar progression to that in culture, with a time lag of at least 6 days between GD3 expression and the onset of myelination. BrdU incorporation studies in vivo also showed that the GD3+ progenitor cell is mitotic wh